Global estimates of incidence of type 1 diabetes in children and adolescents: Results from the International Diabetes Federation Atlas, 10th edition - Ogle, Graham D.; James, Steven; Dabelea, Dana; Pihoker, Catherine; Svennson, Jannet; Maniam, Jayanthi; Klatman, Emma L.; Patterson, Chris C. (Diabetes research and clinical practice, 2022)
Type 1 diabetes (T1D) incidence in children and adolescents varies widely, and is increasing in many nations. The 10th edition of the International Diabetes Federation Atlas estimated incident cases in 2021 for 215 countries/territories (“countries”). Studies on T1D incidence for young people aged 0–19 years were sourced and graded using previously described methods. For countries without studies, data were extrapolated from similar nearby countries. An estimated 108,300 children under 15 years will be diagnosed in 2021, a number rising to 149,500 when the age range extends to under 20 years. The ratio of incidence in 15–19 years compared to those aged 0–14 years was particularly high in some countries in sub-Saharan Africa, North Africa/Middle East, and in Mexico. Only 97 countries have their own incidence data, with extrapolation required for some very populous nations. Most data published were not recent, with 27 countries (28%) having data in which the last study year was 2015 or afterwards, and 26 (27%) having no data after 1999. Many countries have recent data but there are large gaps globally. Such data are critical for allocation of resources, teaching, training, and advocacy. All countries are encouraged to collect and publish current data.